1988
DOI: 10.1246/cl.1988.1507
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regioselectivity in the Photoallylation of Electron-Deficient Alkenes by Allylic Silanes

Abstract: The photoreaction of 1-aryl-2,2-dicyanoethenes with allylic silanes in the presence of phenanthrene gave 4-aryl-5,5-dicyano-1-pentenes in high yields. In this photoreaction, the allylic groups were introduced regioselectively at the β-position to cyano group. In contrast, the photoreaction of alkylidenepropanedinitriles with allylic silanes gave products allylated at the α-position to cyano group along with their reduction products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Photoinduced electron transfer (PET) reaction between organosilicon compounds and electron-deficient molecules is a powerful tool for organic synthesis [1][2][3][4][5][6][7][8][9][10][11]. In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced electron transfer (PET) reaction between organosilicon compounds and electron-deficient molecules is a powerful tool for organic synthesis [1][2][3][4][5][6][7][8][9][10][11]. In these photoreactions, radical anions generated from the electron-deficient molecules and carbon radicals generated from radical cations of the organosilicon compounds are postulated as reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Each photoreaction described above takes place through a process termed photoredox sensitization by phenanthrene (Phen) (Scheme 4) [22,23,24,25,26,27]. In the pathway, the excited singlet state of Phen, generated by light absorption, transfers one electron (SET (single electron transfer)) to the electron-deficient alkene 1 to form the phenanthrene radical cation (Phen •+ ) and the alkene radical anion 1 •− .…”
Section: Resultsmentioning
confidence: 99%
“…Because radical ions that serve as intermediates in these processes are short-lived and highly reactive, control of the stereochemistry of these reactions is often difficult [15,16,17,18,19,20,21]. We have previously developed photoallylation and photoreduction reactions of electron deficient alkenes with allyltrimethylsilane that occur via PET pathways [22,23,24]. In addition, we also demonstrated that diastereoselectivity of this process can be achieved by steric control of allyl radical or proton addition to radical anions that are generated from electron deficient alkenes (Scheme 1) [25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These incorporated both a donating moiety with a fragmentable bond (C᎐Si), 8,18-20 and an accepting moiety that would also function as a radical trap, the alkylidenemalonic group. 19 These materials were prepared by Knoevenagel condensation of the appropriate hydroxy aldehydes with either malonodinitrile or diethyl malonate followed by silylation.…”
Section: Resultsmentioning
confidence: 99%